The Impacts of Teachers’ Paralanguage in EFL Classroom - Yunisah Azzahra; Maemuna Muhayyang; Chairil Anwar Korompot (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The research aims to describe and find out the three following objects: (1) the teachers’ paralanguage forms used by teachers in EFL classroom, (2) the way the teachers use their paralanguage in EFL classroom, (3) the impacts of teachers’ paralanguage toward EFL students’ learning motivation. This research used mix method (the QUAL-Quan model). The instruments used in collecting the data were classroom observation, questionnaire and interview. In order to get the sample, the researchers used purposive sampling. There were 2 English teachers and 60 students from two different classes in eleventh grade of SMAN 1 Polewali as the sample of this research. The result of the research showed that teachers used paralanguage which consists of body language and voice tone while teaching in the classroom. The used of paralanguage by the teachers are different in the certain things like movement or posture. The teachers’ paralanguage has positive impact in the teaching-learning process and helped students understand better the content taught. According to the results of the research, it can be concluded that the teachers’ paralanguage during teaching and learning process made students to be motivated to learn, focused their attention to the teachers’ explanations, and made them confidence in participating the learning process. Hence, it is obvious that teachers’ paralanguage is crucial elements to use well by the teachers because it gives contribution to encourage EFL students’ learning motivation.